Taxonomia das espécies neotropicais de Stauropoctonus Brauns, 1889 (Hymenoptera: Ichneumonidae: Ophioninae), com ênfase nas espécies brasileiras - Alessandro Rodrigues Lima (2013)
Stauropoctonus Brauns, 1889 is a small cosmopolitan genus, characterized by the presence of a transverse suture in the mesopleura and by the sharp curved tooth in the distal margin of median and posterior trochantels. Two species are known for the New World: S. bicarinatus (Cushman, 1947) and S. excarinatus (Cushman, 1947), none of which previously collected in Brazil. The available description of S. excarinatus is too short and based only on males. Here a taxonomic study of the Neotropical species of Stauropoctonus was undertaken, with emphasis on the species found in Brazil. This study was based on material collected for this project and on specimens from foreign (type material ) and national collections. Forty-four specimens were examined: 23 males, 20 females, and one wich sex was undetermined, due to lack of the metassoma apex. The two species previously described for the New World are validated, the description of S. bicarinatus was improved, and S. excarinatus was redescribed, with the first record of its females and of its occurrence in Brazil. Besides S. excarinatus, four other species were found in Brazil, and described as new. The study of the male genitalia was performed for the first time in Stauropoctonus and its importance for the delimitation of the species and future phylogenetic studies is discussed. Furthermore, three new morphological indices are proposed to minimize the subjectivity in species descriptions. A dichotomous key is presented for all the species of this genus, with a brief discussion on the status of S. nigritorax.